(untitled) (Journal of Information Systems and Technology Management, 2008)
Ports that have good geographical location, efficient management and value-added services have potential for international leadership, as is the case with the Valencia Port Authority, which figures prominently in the international ranking of container ports. Information systems should stimulate the curiosity of organizations, facilitate the process of participatory decision-making and enhance the ability of the organization to cope with changes in the environment. Changes occurring in the environment fully affect the organization and therefore its computer systems. Through the study of the Business Intelligence Systems at the Valencia Port Authority, we seek to reaffirm the assumptions of the various authors analyzed. In summary, we would like to highlight that for accounting information, in both financial accounting and management accounting, to add value to the strategic processes of firms, it must successfully contribute to the strategic processes of the organization, selecting those aspects of accounting management that are relevant to the strategy of the organization (Álvarez-Dardet et al., 1999). The evolution and transformation undergone by firms in recent decades, with regard to technological progress and variation in production methods, suggests the possible obsolescence of so-called conventional cost systems. These traditional systems do not take into account the impact of the production process automation and the changes occurring in the relative importance of the different components of the cost of the product. Organizations have to develop accounting information towards a strategic orientation in order to provide support for the strategic business processes, evolving the current information supply of financial accounting and incorporating the information provided by management accounting. In this way the accounting information available to organizations will support their strategic processes more efficiently.